Самооцінні висловлення вихваляння як мовний засіб вираження самоідентифікації мовця - Гончар, Катерина Леонідівна; Рогатюк, Алла Євгеніївна; Honchar, K. L.; Rohatiuk, A. Ye. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано проблему ідентифікації та самоідентифікації, а також вербальні форми реалізації самоідентифікації мовця в процесі комунікації. Особлива увага звернена на вивчення ролі самооцінних висловлень вихваляння у вираженні самоідентифікації особистості. Встановлено градуальний характер об’єк¬тивності самопрезентації мовця, досліджено найбільш частотні параметри самооцінки, описано гендерні особ¬ливості самокатегоризації, що реалізуються самоідентифікаційними висловленнями вихваляння в сучасній англійській мові. The article deals with the analysis of the phenomena of identification and self-identification and linguistic means of expressing the self-identification of the speaker in the process of communication. Self-identification is considered as a mechanism of formation of identification in the result of which each person refers himself to a certain social group. Self-identification is a necessary element which ensures harmonic life of a person in a given society, his/her acceptance of the values, norms, traditions existing in a given society. Special attention is paid to the description of the functional peculiarities of the self-evaluative utterances of boasting as one of the major language forms of realization of self-categorization of a speaker .The analyzed utterances are charac¬terized by different forms of idealization of self-concept and they differ as to the parameters of self-identification. Some gendered properties of self-identification expressed by the self-evaluative utterances of boasting are pointed out.
Self-evaluative Utterances of Boasting as a Linguistic Means of Expressing Self-identification of a Speaker
Keywords: ідентифікація; identification; самоідентифікація; self-identification; самооцінні висловлення вихваляння; self-evaluative utterance of boasting